"Thanks for watching". The effectiveness of YouTube vlogendorsements. (April 2019) - Munnukka, Juha; Maity, Devdeep; Reinikainen, Hanna; Luoma-aho, Vilma
Abstract: This study examines the effectiveness of brand endorsements in vlogs (video blogs) by assessing the role of audience participation, parasocial relationship, and valence toward vlog endorsements on the perceived credibility of the vlogger and brand attitudes. Four experimental conditions were created on Qualtrics based on a YouTube vlog where the endorser reviewed a few products. The data were collected using Mturk and analyzed with 203 usable responses. The findings indicate that audience participation in the vlog enhances para-social relationship with the vlogger, thus further fostering the vlogger's perceived credibility as an endorser. Additionally, the valence of the audience's attitudes toward vlog endorsements moderates the audience participation–parasocial relationship. The results show that vlogs with high levels of audience participation are more likely to increase the acceptance of the brand's endorsement via enhanced credibility perceptions among viewers. Hence, time should be spent choosing vloggers who are active in the online community. This study contributes to the understanding of the distinct characteristics of vlogs that specifically affect endorsement effectiveness. The focal role of parasocial relationship for message acceptance in the context of vlogs is also highlighted.